(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
Malaria remains among the most common illnesses caused by parasites of the Plasmodium spp. It still poses a serious risk to millions of people living in both tropical and subtropical regions, causing thousands of deaths. The antimalarial activity of decoction from Mangifera indica, Carica, and Psidium guajava leaves in Plasmodium berghei inoculated mice was evaluated. Forty-nine mice averaging 22 g were grouped into 7 groups (7 per group). Group 1 served as naïve control, Groups 2–6 received intraperitoneal injections containing 1.0 x 107 red blood infected with Plasmodium berghei. Administration of 100, 150, and 300 mg/kg body weight of the decoction to groups 4, 5, and 6 respectively was done daily after infection with the parasite was confirmed. Group 2 received no treatment, while Group 3 received four days of treatment with 20 mg/kg body weight of chloroquine. Group seven was decoction control (300 mg/kg body weight). The mice were sacrificed after the treatment and blood and liver tissue were collected for analysis. Phytochemical constituents of the decoction and its LD50 were also determined. The decoction was found to contain appreciable amounts of phenolics, tannins, and alkaloids along with other phytochemicals and the calculated LD50 was 5720 mg/kg body weight. Treatment with the decoction caused substantial decrease (p < 0.05) in parasite count within groups that received treatment compared to untreated ones and significantly (p < 0.05) improved biochemical parameters altered by malaria. The findings of this study revealed that the decoction is effective in management of malaria.